A comparison of input- and output-based planning on the oral performance of low proficiency EFL learners. (November 2022) - Lee, Dongju; Kim, Sung-Yeon
Abstract: This study aims to compare the effects of input- and output-based planning on the oral performance of low-proficiency EFL college students. The purpose is to evaluate the received wisdom that output-based tasks used in task based instruction (TBI) do not fit low-level learners. For data collection, 168 Korean female college students with limited English proficiency were divided into two groups: a reading group and a writing group. The two groups received the same instruction, but the planning tasks differed for oral performance. The reading group had input-based planning, for which the students read example answers prior to speaking performance. In contrast, the writing group or the output-based planning group performed the same tasks after writing what they wanted to say. The students' performance on the pre- and post-test was compared in terms of complexity, accuracy, and fluency (CAF) measures. The findings showed statistically significant differences between the two groups in terms of their speaking scores and the fluency measures, with the writing group outperforming the reading group. The follow-up interviews with the students and their reflection journals also confirmed the facilitative effects of output-based planning. These findings indicate how beneficial output-based planning can be for developing low-proficiency learners' oral fluency.